Evaluation of the viewpoints of faculty members regarding to research barriers at Babol dental school - Maryam Seyyedmajidi; Sorayya Khafri; Shabnam Sohanian; Seyyd Ali Seyyedmajidi (Babol University of Medical Sciences, 2018)
BACKGROUND AND OBJECTIVE: Research is one of the major fundamental in the development of human societies. Failure understanding and awareness of the goals of research programs including essential tools that should be delivered to policy makers of research. METHODS: This descriptive cross-sectional study was carried out to determine barriers to research from viewpoint of faculty members of the School of Dentistry, Babol University of Medical Science in 2015. To collect data, a questionnaire consisted of demographic and items in five-point sets up. To analyze the data, related statistical tests were used. SPSS version 20 software used and significant level was considered 0.05. FINDINGS: Socio-cultural field with highest score was the most barrier field and compiled project field with lowest score known as lowest barrier between other fields. Mean score of items between of the field of compiled project and socio-cultural with other fields, mean score of items of socio-cultural field between males and females and mean score of items of compiled project and socio-cultural fields between different educational groups showed significant statistical difference. CONCLUSION: Researchers in any scientific discipline according to their own experiences and other researchers, must reveal weaknesses and shortcomings. So are recommended research managers take action by results of this research in removing barriers to research and promote the university level.